PENGUKURAN KESESUAIAN ANTARA BISNIS DENGAN TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT - Ichsan Taufik; Adam Faroqi (JURNAL ISTEK, 2012)
Current information technology at PT XYZ is a valuable asset for the company to achieve business goals. Information Technology Division leaders intend to measure the extent of correspondence between the information technology and business that is owned. The method used in measuring the level of compliance is IT Governance COBIT framework. The result is to give recommendations for the strengthening of IT services in the PT XYZ to be more effective.